2022
DOI: 10.1371/journal.pone.0264147
|View full text |Cite
|
Sign up to set email alerts
|

Growing up in the Betsileo landscape: Children’s wild edible plants knowledge in Madagascar

Abstract: Understanding local knowledge about wild edible plants (WEP) is essential for assessing plant services, reducing the risks of knowledge extinction, recognizing the rights of local communities, and improving biodiversity conservation efforts. However, the knowledge of specific groups such as women or children tends to be under-represented in local ecological knowledge (LEK) research. In this study, we explore how knowledge of WEP is distributed across gender and life stages (adults/children) among Betsileo peop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 71 publications
3
13
0
Order By: Relevance
“…As seen in our results, children know different species and methods of WEP preparation than adults and de ne important WEPs differently. This nding is not new, as similar ndings were observed across small-scale societies and ecological regions including two cases in Madagascar (Gallois et al, 2017;Tucker & Young, 2017;Porcher et al, 2022). Thus, our insights reinforce the idea that children hold specialised 'knowledge and -potentiallywhat has been called "a children's culture" (Johanson, 2010;Gallois et al, 2017).…”
Section: Intracultural Variation Through Life Stage and Gender Lensessupporting
confidence: 83%
See 1 more Smart Citation
“…As seen in our results, children know different species and methods of WEP preparation than adults and de ne important WEPs differently. This nding is not new, as similar ndings were observed across small-scale societies and ecological regions including two cases in Madagascar (Gallois et al, 2017;Tucker & Young, 2017;Porcher et al, 2022). Thus, our insights reinforce the idea that children hold specialised 'knowledge and -potentiallywhat has been called "a children's culture" (Johanson, 2010;Gallois et al, 2017).…”
Section: Intracultural Variation Through Life Stage and Gender Lensessupporting
confidence: 83%
“…Knowledge distribution has been discussed as social-risk management strategy, potentially contributing to resilience in local systems: The more distributed is the knowledge within a population, the more likely this population would be able to deal with disturbance (Blanco & Carrière, 2016). Nevertheless, as bodies of knowledge differ across and within social groups, gender, and age (Diaz Reviriego et al, 2016; Porcher et al, 2022), it is also important to explore the knowledge held by different sub-groups of the population, as the diversity of their knowledge can contribute to the resilience of the knowledge system (Diaz Reviriego et al, 2016). For example, Gallois et al, 2017 concluded that children from different small-scale societies hold speci c bodies of knowledge, not necessarily shared by adults, and Crittenden (2015) stated that children's knowledge about WEP contribute to the food system by actively engaging foraging activities.…”
Section: Introductionmentioning
confidence: 99%
“…The above-mentioned discussion shows that cultural learning in childhood goes through different stages in its development. On the one hand, it is heavily influenced by adult references who are relatives, as well as by pre-established rules of gender and social dynamics in places where children and adolescents grow up [ 63 , 68 , 69 ]. On the other hand, they have the autonomy to actively search for solutions and acquire knowledge about things in the environment to share with their peers between games and other joint activities [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…This process is marked by questions of trial-and-error, testing of hypotheses, and imitation, which is characteristic of this phase of development. These results may also relate the factors related to the act of children sharing aspects of a culture [ 67 , 69 ]. In children culture, the factors for considering the importance of a medicinal plant may have nothing to do with those considered by adults.…”
Section: Discussionmentioning
confidence: 99%
“…For (at least some) children in Fiji and New Caledonia, fishing—as a mode of “active engagement with the constituents of [their] surroundings” (Ingold 2000 , p. 5), namely of land-sea territories—represents a way of knowing marine environments and their various dwellers. In particular, these children often go fishing with relatives or friends, which allows for intra- and/or inter-generational learning, through horizontal and/or vertical mechanisms of knowledge transmission (Porcher et al 2022 ). Despite observations that IFK is increasingly threatened in the Pacific (Kitolelei et al 2021 ), our study shows that its transmission through hands-on experiences is still occurring, and that children’s interest in learning IFK is palpable.…”
Section: Resultsmentioning
confidence: 99%